MANAJEMEN PENGADAAN BARANG DAILY MARKET LIST PADA CULINARY DEPARTMENT OLEH PURCHASING DI HOTEL A - Eva Selviani; Cokorda Gede Putra Yudistira; I Gusti Ketut Gede (Berajah Journal, 2026)
This study aims to analyze the implementation of the Planning, Organizing, Actuating, and Controlling (POAC) management functions in the procurement of Daily Market List items for the Culinary Department by the Purchasing Department at A hotel, identify the obstacles encountered during the procurement process, and examine the efforts undertaken to overcome these obstacles. This study employed a descriptive qualitative method with a case study approach. Data were collected through observation, interviews, and documentation involving the Purchasing Manager, Purchasing Staff, and Receiving staff at Hotel A. Data were analyzed using the interactive analysis model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of the POAC management functions in the procurement of Daily Market List items has been carried out effectively and in accordance with established procedures. This is reflected in procurement planning based on the Daily Market List, clear task allocation and coordination among departments, the implementation of procurement activities following operational procedures, and control through quality and quantity inspections as well as periodic supplier performance evaluations. However, several obstacles remain, including delays in the Daily Market List approval process, late deliveries from suppliers, limited product availability, fluctuations in food ingredient prices, and discrepancies in the quality and quantity of delivered goods. To address these challenges, the Purchasing Department maintains intensive coordination with the Culinary Department and suppliers, utilizes alternative suppliers, identifies suitable substitute ingredients, and conducts regular supplier performance evaluations. These efforts are expected to improve the effectiveness and efficiency of the procurement process, thereby supporting the smooth operation of the Culinary Department at Hotel A.